YES(?,O(n^2)) Problem: g(f(x),y) -> f(h(x,y)) h(x,y) -> g(x,f(y)) Proof: RT Transformation Processor: strict: g(f(x),y) -> f(h(x,y)) h(x,y) -> g(x,f(y)) weak: Matrix Interpretation Processor: dimension: 1 interpretation: [h](x0, x1) = x0 + x1 + 31, [g](x0, x1) = x0 + x1 + 2, [f](x0) = x0 orientation: g(f(x),y) = x + y + 2 >= x + y + 31 = f(h(x,y)) h(x,y) = x + y + 31 >= x + y + 2 = g(x,f(y)) problem: strict: g(f(x),y) -> f(h(x,y)) weak: h(x,y) -> g(x,f(y)) Matrix Interpretation Processor: dimension: 2 interpretation: [1 1] [1 0] [9] [h](x0, x1) = [0 1]x0 + [0 0]x1 + [0], [1 1] [1 0] [3] [g](x0, x1) = [0 1]x0 + [0 0]x1 + [0], [6] [f](x0) = x0 + [7] orientation: [1 1] [1 0] [16] [1 1] [1 0] [15] g(f(x),y) = [0 1]x + [0 0]y + [7 ] >= [0 1]x + [0 0]y + [7 ] = f(h(x,y)) [1 1] [1 0] [9] [1 1] [1 0] [9] h(x,y) = [0 1]x + [0 0]y + [0] >= [0 1]x + [0 0]y + [0] = g(x,f(y)) problem: strict: weak: g(f(x),y) -> f(h(x,y)) h(x,y) -> g(x,f(y)) Qed